The role of Australian First Nations’ Knowledges and the arts in “inclusive” regional and remote development: A narrative review - Sunderland, Naomi; Woodland, Sarah; O'Sullivan, Sandy; Bartleet, Brydie-Leigh (Journal of Rural Studies, 2021)
This paper offers a narrative review of existing academic and grey literature on the roles of Australian First Nations' Knowledges and the arts in regional and remote development. We do so to examine the degree to which current mainstream approaches to development are actualising international calls for “inclusive” development that accentuate “Indigenous” local and knowledges and strengths. The paper discusses existing regional and remote development literature through a lens of holistic, strength-based, and inclusive development. This incorporates many forms of valuing and developing including: cultural, social, environmental, and economic forms of value and activity. We conclude by offering recommendations for future research, policy, and practice that can draw on the strengths of First Nations’ Knowledges and the arts to achieve inclusive and holistic development. No Full Text